Configuration of Physical and Mechanical Characteristics of Concrete with Calcium Lactate Inclusion - Saddam Hussein Abo Sabah; Mohd Irwan Juki; Anneza Luis Hii (2023)
Over the year, the concrete life span has become a major concern in the construction industry, specifically, when concrete structure exposed to aggressive environments. Concrete incorporating with waste material has been widely conducted in order to improve the concrete deterioration. This book is an originally published for the first edition from Universiti Tun Hussein Onn Malaysia. Target audiences for this book are the academics, researchers and students who seek for a deep information on the inclusion of calcium lactate in bio-concrete. Properties of bio-concrete with the addition of calcium lactate consists of four chapters. The chapters are mostly devoted to highlight the effect of calcium lactate on the mechanical and durability properties of bioconcrete. This finding is a vital topic to ensure the sustainability of concrete structure. Each chapter is presented with tables and graphs to encourage better understanding and visualization in this topic. List of references is attached at the end of each chapter for further information. We are deeply grateful to all the reviewers for their time and constructive comments.